Sérgio Sampaio e a paródia tropicalista em Eu quero é botar meu bloco na rua - Araújo, Luís André Bezerra de (2009)
The Tropicalismo figured in 1967 and 1968 as an artistic activity that has opened new ways for the Brazilian art. The acknowledgment of the tropicalist intervention as a vanguardist art has already been analyzed by excellent researches. This work has another goal: we begun with Tropicalismo (only its musical works) and we stopped with the first recorded work from the composer Sérgio Sampaio, Eu quero é botar meu bloco na rua, in 1973. When that work was released, the reviewers told it excessively inclined to the tropicalist influence and they were not capable of seeing the inherent procedures on Sampaio s songs. Here in this work, we establish a parodic relationship (under the perspectives proposed by Mikhail Bakhtin, Haroldo de Campos and Severo Sarduy) between Sergio Sampaio s songs and the tropicalist aesthetics. Considering that the object of our research is the song, we rely on the reflexions of Luiz Tatit about diction on the popular Brazilian music in XX century.